Treatment Costs of Matrix-Associated Autologous Chondrocyte Implantation Compared With Microfracture: Results of a Matched-Pair Claims Data Analysis on the Treatment of Cartilage Knee Defects in Germany. Issue 12 (5th December 2019) - Niemeyer, Philipp; Schubert, Tino; Grebe, Marco; Hoburg, Arnd
Background: Articular cartilage damage is caused by traumatic sport accidents or age-related degeneration and might lead to osteoarthritis, which represents a socioeconomic burden to society. Cartilage damage in the knee is commonly treated surgically with microfracture (MFX) or matrix-associated autologous chondrocyte implantation (MACI). Purpose: To quantify the initial and follow-up costs associated with MFX and MACI treatments from the viewpoint of statutory health insurance in Germany. Study Design: Economic decision analysis; Level of evidence, 2. Methods: This comparative study was based on an anonymized representative claims data set of 4 million patients covered by statutory health insurance in Germany. Patients undergoing outpatient or inpatient treatment with MACI or MFX for cartilage damage in the knee between January 1, 2012, and December 31, 2013, were included and evaluated over 5 years. Groups (MACI and MFX) were adjusted via propensity score matching before initial treatment. The matched groups were compared regarding their outpatient, inpatient, pharmaceutical, and other costs during the 5-year period. Results: In total, 127 patients per group were analyzed (59.1% male, 40.9% female; mean age, 37 years). In the year of the initial surgical procedure, costs were €14, 804.13 in the MACI group and €5458.59 in the MFX group. In years 2 and 3 after initial surgery, treatment costs were comparable between patients treated with MACI (€2897.97 and €2114.87, respectively) and MFX (€2842.66 and €1967.42, respectively), with slightly higher treatment costs for those treated with MACI. In years 4 and 5 after surgery, costs were less in patients treated with MACI (€2154.79 and €1478.08, respectively) than in those treated with MFX (€2232.57 and €2061.63, respectively). Costs related to revision surgery were, on average, €3732 for MACI and €3765 for MFX. Thus, additional costs in years with revision surgery were €1672 for MACI and €1915 for MFX. Conclusion: This was the first study to analyze a large representative population claims database with propensity score matching, and results indicated that follow-up costs of patients treated with MACI and MFX began to converge over time. We found that total costs for MACI were higher than for MFX but that additional costs for MACI were lower than previously reported. Perceived morbidity may have little to do with cost.